Oral administration of Bali Robusta coffee (Coffea canephora) extract prevented the reduction of Leydig cells and testosterone levels in male Wistar rats (Rattus norvegicus) with excessive physical training - Kandy Rosa Ismalia; Wimpie Pangkahila; Ni Putu Sriwidyani (Neurologico Spinale Medico Chirurgico, 2021)
Background: Excessive exercise cause a deterioration of organ function and structure. Overtraining will cause reduce antioxidant reserve and excess free radical production. In this condition, there will be a decrease in the number of Leydig cells in the testis and followed by a decrease in testosterone level. Bali robusta coffee extract contains active compounds such as alkaloids, saponins, flavonoids, tannins and polyphenols. This study aims to prove whether Bali robusta coffee extract (Coffea canephora) can prevent a decrease in the number of Leydig cells and testosterone levels in male Wistar rats (Rattus norvegicus) with excessive physical training. Methods: Thirty-six rats were randomly divided into 2 groups: the control group (placebo aquabidest 2 ml) and the treatment group (Bali robusta coffee extract of 1 gram/kg BW). Both groups received excessive physical training in the form of swimming until the subjects experienced fatigue for 21-days. Results: The results showed that the mean of Leydig cell number in the treatment group was significantly higher, which was 3.70 ± 0.89 cell/field of view, compared to the control group, which was 2.92 ± 0.65 cell/field of view (p = 0.005). The mean testosterone level in the treatment group was also significantly higher, which was 6.32 ± 0.21 nmol/ml, compared to the control group, which was 1.95 ± 0.32 nmol/ml (p < 0.001). Conclusion: The administration of Bali robusta coffee extract (Coffea canephora) prevented a decrease in the number of Leydig cells and testosterone levels in male Wistar rats (Rattus norvegicus) with excessive physical training.